Nitrogen Deposition and Leaching from Two Forested Catchments in Southwest China — Preliminary Data and Research Needs - T. Larssen; J. Mulder; Y. Wang; X. Chen; J. Xiao; D. Zhao (The Scientific World Journal)
Increased nitrogen deposition has resulted in increased nitrogen pools and nitrogen leaching in European and North American forest soils. The development in Asia in general, and China in particular, suggests increased deposition of reduced nitrogen from changes in agricultural practices and of oxidized nitrogen from rapid growth of the transportation sector. Decreased nitrogen retention in forested areas in the future may cause increased NO3– leaching and, thus, acidification and eutrophication in surface waters. The differences in climate, ecosystems, land use, and deposition history make direct application of knowledge from studies in Europe and North America difficult. In Southwest China the potential for nitrogen mobilization from forest soils may be high because of the warm and humid climate, resulting in high decomposition rates of soil organic matter. However, there are very few data available for quantifying the suspected potential for increased nitrogen leaching in forest ecosystems. Here we present data from two forested catchments, dominated by Masson pine (Pinus massoniana), near Guiyang and Chongqing, respectively, in Southwest China. The present nitrogen deposition is moderate, estimated in the range from 10 to 40 kg N ha–1 year–1. The C/N ratios of the soils are generally below 15. Nitrate concentrations in soil water are rather variable in space, with highest values of several hundred microequivalents per liter. The turnover rate of nitrogen in the forest ecosystem is quite high compared to the atmospheric deposition rate. At present, nitrate runoff from the catchments is low and intermediate in Guiyang and Chongqing, respectively. More research is needed to improve our ability to predict future nitrogen leaching from subtropical Asian coniferous forests.